INTRODUCING THE VALUES OF PANCASILA FOR THE TOPIC OF SPEAKING IN ENGLISH 1 SUBJECT AT STATE POLYTECHNIC OF SRIWIJAYA - Koryati; Deri Darfin; Nian Masna Evawati (Politeknik Negeri Sriwijaya, 2022)
The aim of this study was to discuss the values of Pancasila and how to introduce them to the students toward speaking activities as part or the topic of conversation. The values of Pancasila were broken down into five values which follows the Guidelines for the Implementation and Practice of Pancasila in Decree of People's Consultative Assembly of Republic of Indonesia or known as Ekaprasetia Pancakarsa. The topic of the conversation for the speaking practice were determined and composed based on the Ekaprasetia Pancakarsa. The Guidelines for the Implementation and Practice of Pancasila in Decree of People's Consultative Assembly of Republic of Indonesia consist of moral principles such as likes to work hard, likes to help others, appreciates other’s work, etc which would be used as the topic of the conversation or part of the conversation by composing sentences related to specific sentences in describing into working hard, helping others, appreciating other’s work, etc so later they can be used to encourage the students to use the sentences in speaking practice. Keywords: values of Pancasila, guidelines, ekaprasetia pancakarsa, speaking, conversation topic